The Language of Fact-Checking: Critical Literacy Practices in Indonesian News Portals - Hafiza Saumi Ramadilla; Halimah Br Surbakti; Elisabeth Monica Hutahaean; Rifana Dwi Dywanti Hasibuan; Dimas Abdul Ramadan; Muhammad Natsir (Pusat riset dan Inovasi Nasional, 2025)
In the digital age, information travels quickly, which has made it easier to learn new things but also made it easier for false information to spread. In Indonesia, fact-checking efforts by online news sites like Kompas, Tempo, and Liputan6 have become very important in dealing with this problem. This study examines the linguistic and discursive strategies utilized in fact-checking articles published from 2022 to 2024 to foster critical literacy among readers. Utilizing the principles of Critical Literacy and Critical Discourse Analysis (CDA), the study examines five fact-checking texts addressing political, health, and social matters. The results show that all the articles follow the same story structure: they start with claims, then go into detail about the investigations, present evidence, and give final judgments. At the micro level, hedges, boosters, and evidential markers are used on purpose to change how certain and credible something is. At the meso level, discourse structures and intertextual references bolster institutional authority, whereas at the macro level, fact-checking serves as an educational instrument that promotes critical and contemplative reading habits. Overall, the study shows that fact-checking serves two purposes in Indonesia: it helps people check the accuracy of information and it helps people build their resistance to false information.